Barrier-free duct muffler for low-frequency sound absorption - Gao, Cong; Hu, Chuandeng; Mei, Jun; Hou, Bo; Zhang, Xianli; Du, Zhanhang; Wen, Weijia (Frontiers in Materials, 2022)
We demonstrate a duct muffler design that operates in the low-frequency range (<2000 Hz). The device contained a pair of coupled annular Helmholtz resonators (HRs) and porous material stuffing. HRs were installed as side branches of a circular tube to avoid affecting the ventilation. Porous materials were employed to form an asymmetric intrinsic loss in the HR pair and enable the device to achieve perfect sound absorption. An analytical model based on the temporal coupled-mode theory was derived, and a numerical simulation technique for structural design was introduced and verified. The experimental study demonstrated the effectiveness of the design methodology and illustrated that the device can achieve near-perfect sound absorption in the desired frequency range. A symmetrical configuration of the HRs also experimentally proved to be able to conduct sound absorption for sound incident from both sides of the duct. This study provides a solid foundation for the application of the designed muffler and an analytical explanation of the corresponding sound absorption mechanisms.